Textual Commentaries to "The Man in the Panther Skin": Summarizing the Rustavelian Theory of Poetry - Khintibidze, Zaza (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
There are two reasons, due to which the need arises for a novel interpretation of the 17th stanza from the Prologue to The Man in the Panther Skin: 1) it is necessary to clarify or even revise N. Marr’s interpretation of the above stanza, which was recognized to be correct by researchers of Rustaveli’s poem in order to explain in any possible way the apparent consequential inconsistency that seems to exist between the second half-line of 17.4 (17.4b) and the first half-line of 12.4 (12.4a); 2) within the framework of the 17th stanza several peculiarities of various types are observed, which require explanation. The study conducted in the above-indicated direction revealed, that - as opposed to one of the newly proposed scholarly assumptions - the 17th stanza, as expected, not only cannot be regarded as a later insertion in the text of the poem, but it brings together and summarizes Rustaveli's whole aesthetic conception, reflected in the form of a unified discourse within all six stanzas (12-17) depicting the Rustavelian theory of poetry.